Vicarious Lives: The Controlling Mother in Philippine and Japanese Fiction - Sabanpan-Yu, Hope (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper focuses on works that highlight the ’vicarious’ mother. The female protagonists in the texts under consideration manipulate their children to carry out their selfish plans to achieve their own goals within the patriarchal dominance. Enchi’s A Tale of False Fortunes and Masks together with Hirabayashi’s "A Woman to Call Mother," Montaire’s Ikaduhang Sugo and Espina-Moore’s Inahan ni Mila are five of the most representative works that narrate this kind of maternal control. These works are extremely complex, multi-layered novels exploring exploitation of children by mothers.